Microbial electrolysis cells for decentralisedwastewater treatment: The next steps - Fudge, Thomas; Bulmer, Isabella; Bowman, Kyle; Pathmakanthan, Shangami; Gambier, William; Dehouche, Zahir; Al-Salem, S. M.; Constantinou, Achilleas (My University, 2021)
Traditional wastewater treatment methods have become aged and inefficient, meaning alternative methods are essential to protect the environment and ensure water and energy security worldwide. The use of microbial electrolysis cells (MEC) for wastewater treatment provides an innovative alternative, working towards circular wastewater treatment for energy production. This study evaluates the factors hindering industrial adoption of this technology and proposes the next steps for further research and development. Existing pilot-scale investigations are studied to critically assess the main limitations, focusing on the electrode material, feedstock, system design and inoculation and what steps need to be taken for industrial adoption of the technology. It was found that high strength influents lead to an increase in energy production, improving economic viability; however, large variations in waste streams indicated that a homogenous solution to wastewater treatment is unlikely with changes to the MEC system specific to different waste streams. The current capital cost of implementing MECs is high and reducing the cost of the electrodes should be a priority. Previous pilot-scale studies have predominantly used carbon-based materials. Significant reductions in relative performance are observed when electrodes increase in size. Inoculation time was found to be a significant barrier to quick operational performance. Economic analysis of the technology indicated that MECs offer an attractive option for wastewater treatment, namely greater energy production and improved treatment efficiency. However, a significant reduction in capital cost is necessary to make this economically viable. MEC based systems should offer improvements in system reliability, reduced downtime, improved treatment rates and improved energy return. Discussion of the merits of H2 or CH4 production indicates that an initial focus on methane production could provide a stepping-stone in the adoption of this technology while the hydrogen market matures.
Keywords: Wastewater treatment; Microbial electrolysis cell; Methane production; Hydrogen production; Waste management; Cathode; Anode; Water research; Renewable energy